Penciptaan dan Hak Kepemimpinan Perempuan dalam Al-Qur'an - Muhammad Yusuf (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2013)
This article investigates muslims scholars’ views about women’s creation and their right of leardership based on the Qur’an. Various methods of exegesis of the Qur’an influences significantly in understanding the women’s creation and their right of leadership. The failure to find out ideal impression of the verses of the Qur’an is This article investigates Muslims scholars’ views concerning creation of women and their leadership right in accordance with the Qur’an. Various methods of Qur’anic exegesis significantly influence understanding of the creation of women and their right of leadership. Failure to disclose the ideal impression of the Qur’anic verses is majorly caused by separation of its texts and contexts. A historical awareness and external reality today are two in each other's pocket variables. Another factor is hadith (riwayat) from an ahlul kitab who converted to be a Muslim and recounts that Hawa was created from Adam’s left bent rib bone. Whereas according to the Qur’an humankinds, both men and women, have originally been created from the same source in that they share equal position, and men cannot subordinate women. Nor are they competitors one another, rather they are partners with own virtues and women to serve as public leaders as long as they fulfill qualitative criteria of competences, including those of the managerial, leadership, intellectual, personal, and also of course, with a public support.